COMBINED CONVENTIONAL AND COMPLEMENTARY THERAPY ON BREAST CANCER PATIENTS’ QUALITY OF LIFE: A CROSS-SECTIONAL STUDY IN BALI - Dewi Puspita Apsari; Dhiancinantyan Windydaca Brata Putri (Journal Pharmaceutical Science and Application, 2025)
Background: Complementary and Alternative Medicine (CAM) is widely adopted by female breast cancer patients seeking to improve their health-related quality of life. However, research related to the quality of life of breast cancer patients who use CAM is still ambiguous and has never been done in Indonesia. Objective: This study aims to compare the quality of life between breast cancer patients who use conventional therapy (chemotherapy) with a combination of conventional therapy and CAM. Methods: This cross-sectional study was conducted on 80 women who underwent chemotherapy at least one cycle at RSUD Sanjiwani, Gianyar. Participants were divided into two groups: those treated with conventional therapy only, and those who also incorporated CAM therapies such as massage, herbal medicine, and spiritual healing practices. Assessment of quality of life in patients was conducted using the standardized EORTC QLQ-C30 questionnaire developed by the European Organisation for Research and Treatment of Cancer. Quality-of-life scores between groups were compared using an independent t-test. Results: The results showed that there were significant differences in breast cancer patients who used conventional therapy (chemotherapy) with a combination of conventional therapy and CAM in the domain of global health status (61, 67 vs 71.67, p=0.000), cognitive functioning (54.33 vs 27.67, p=0.000), role functioning (53.33 vs 29.33, p=0.009), fatigue (35.22 vs 24.44, p=0.000), nausea and vomiting (74 vs 45.67, p=0.000) and pain (85.67 vs 52.33, p=0.000). Conclusion: The combination of conventional therapy and CAM significantly improved global health status and symptom management in breast cancer patients, suggesting its potential to enhance quality of life alongside standard treatment. Keywords:  Breast Cancer; Complementary and Alternative Medication (CAM); Conventional; EORTC QLQ-C30; Quality of Life.